Granting Exclusive Breastfeeding Certificate to Increase Maternal Motivation for Exclusive Breastfeeding - Dian Nurafifah; Ratih Indah Kartikasari; Ihda Mauliyah; Andri Tri Kusumaningrum (Universitas Nahdlatul Ulama Surabaya, 2022)
The World Health Organization (WHO) and the United Nations International Children'sEmergency Fund (UNICEF) have recommended exclusive breastfeeding, but there arestill mothers who do not provide exclusive breastfeeding. In 2018, its number was only37.3%, while the government's target of exclusive breastfeeding coverage of 80%. Oneeffort to support exclusive breastfeeding mothers is giving certificates. This study aimsto determine the correlation between granting exclusive breastfeeding certificates andmaternal motivation for exclusive breastfeeding. It was a correlational study with across-sectional design. The independent variable was granting exclusive breastfeedingcertificates, while the dependent variable was maternal motivation for exclusivebreastfeeding. The population was breastfeeding mothers for more than six months inBedingin Village, Sugio District, Lamongan Regency. The samples were 40 respondentswith simple random sampling. We interviewed respondents with a questionnaire as aresearch instrument. Then, data analysis used the Chi-Square test with α = 0.05. 87.9%of mothers who received exclusive breastfeeding certificates had good motivation forexclusive breastfeeding. In addition, the Chi-Square test obtained p=0.000 (α˂0.05).Thus, there was a significant correlation between granting exclusive breastfeedingcertificates and maternal motivation for exclusive breastfeeding. In conclusion,awarding exclusive breastfeeding certificates increase maternal motivation for exclusivebreastfeeding. Further, it could improve coverage of exclusive breastfeeding inIndonesia. The local government should make policies in issuing exclusivebreastfeeding certificates.